A comunicação jurídica e seu impacto para o exercício da cidadania: uma análise a partir do campo da ciência, tecnologia e sociedade - Monteiro, Gabriella Henrique Targino (2024)
This research aims to discuss the legal community's difficulty in establishing effective communication with citizens, hindering the full exercise of citizenship. To this end, it seeks to analyze the aspects of legal communication, as well as its effects, from an interdisciplinary perspective, or, better said, multidisciplinary, constructing a critical analysis from an ethical, social, cultural, political, philosophical, legal and STS point of view, with the aim of understanding the aspects that make it difficult for citizens to understand the law. The investigation has a qualitative character and uses the hypothetical-deductive approach method in its development, mainly through the use of books, papers, dissertations and theses on the topic. Finally, we conclude that the communication failure that occurs between the legal system and citizens results in a non-recognition of the Judiciary as an instrument that guarantees citizens' rights and their well-being. Thus, citizens see themselves as hostages of a Judiciary that works in favor of the few who can understand it. Faced with this problem, movements began to emerge from the institutions that make up the Judiciary to make legal communication more accessible and inclusive, however, there is still much to be done.